Repairing fishing nets for the next fishing expedition - Mumbai Archive Project Team (Jio Institute, 2024)
After a brief stint at home, Rakesh and Rahul Bhalia return to the coast to prepare for the next fishing expedition. They meticulously clean the boat, removing debris to ensure a clean working space. They inspect and repair fishing nets, lines, and other equipment to ensure they are undamaged. In the photo, Rakesh is seen crafting a new oar to replace the worn-out one.